Outcome of long-term complications after permanent metallic left bronchial stenting in children. (8th November 2017) - Serio, Paola; Nenna, Raffaella; Di Maurizio, Marco; Avenali, Stefano; Leone, Roberto; Baggi, Roberto; Arcieri, Luigi; Murzi, Bruno; Quarti, Andrea; Pozzi, Marco; Mirabile, Lorenzo; Midulla, Fabio
Abstract: OBJECTIVES: We describe the way we treated 7 children with critical long-term complications after metallic balloon-expandable stenting in the left mainstem bronchus. METHODS: Endoscopic follow-up included a first bronchoscopy 3 weeks after stenting, then monthly for 3 months, every 4–6 months up to 1 year and at scheduled times to calibrate stent diameter up to final calibration. When major complications occurred, patients underwent chest computed tomographic angiography. RESULTS: In 1 of the 7 children (median age 2.8 years), metallic left bronchial stenting served as a bridge to surgery. After a median 4-year follow-up, all 7 children experienced recurrent stent ovalizations with stent breakage in 3 and erosion in 1. In 4 children, computed tomographic angiography showed abundant peribronchial fibrous tissue, in 2 left mediastinal rotation and in 1 displacement along the left bronchus after pulmonary re-expansion as the cause of stent-related complication. Of the 7 children, 6 underwent surgery (5 posterior aortopexy and 1 section of the ligamentum arteriosus) and 3 required nitinol stents placement within the metallic ones. One patient completed the follow-up, and 1 patient was lost to follow-up. All 5 remaining children still have permanent bronchial stents in place, patent and re-epithelialized after a median 10.5-year follow-up. There were no deaths. CONCLUSIONS: Satisfactory anatomical relationships when children have stents placed in the left mainstem bronchus alone do not guarantee the final success. Several mechanisms intervene to cause critical stent-related complications in children during growth. Permanent metallic stents should be used carefully, and only in selected patients.